PENGARUH CSR, PROFITABILITAS, DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SEKTOR PERKEBUNAN YANG TERDAFTAR DI BEI - NATALIA, YOHANA FRANSISKA; RACHMAWATI, TITIEK; RAHMIYATI, NEKKY (GANEC SWARA, 2024)
The research objectives to be achieved in accordance with the problem formulation described above are to analyze: (1) The influence of corporate social responsibility on company value in plantation sector companies listed on the BEI in 2019 - 2021. (2) The influence of profitability on company value in plantation sector companies listed on the BEI in 2019 – 2021. (3) The effect of company size on company value in plantation sector companies listed on the BEI in 2019 – 2021. (4) What are corporate social responsibility, profitability and company size together? – the same has a significant effect on the company value of plantation sector companies listed on the IDX in 2019 – 2021. The population used in this research consists of 24 plantation sector companies listed on the Indonesia Stock Exchange (BEI) in the 2020-2022 period. Purposive sampling technique was used in sampling, so that 10 plantation sector companies were obtained. The analysis technique used in this research is multiple linear regression to test the hypothesis. The results of the analysis findings conclude that 1) partially corporate social responsibility has a positive effect on company value; 2) partially profitability has a positive effect on company value; 3) partially company size has a positive effect on company value; 4) simultaneously has a positive effect on company value